A study of lipid profile peculiarities and atherogenic index of plasma in patients younger than fifty years of age with newly diagnosed rheumatoid arthritis - Varsha R. Bhatt; Kavita K. Krishna; Vishal Asrani; Rajat Chauhan (Journal of Family Medicine and Primary Care)
Context: Cardiovascular disease (CVD) is an important cause of mortality in rheumatoid arthritis (RA). Aims: Evaluation of lipid profile and atherogenic index of plasma (AIP) in newly diagnosed DMARD naïve patients of RA younger than 50 years of age, and its comparison with age- and sex-matched healthy controls. Settings and Design: Cross-sectional comparative study. Methods and Material: 48 patients aged 18 to 50 years fulfilling the ACR/EULAR criteria for RA, not yet on DMARD or steroids and 51 healthy controls were included. Disease activity was assessed, and lipid profile was estimated: total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides (TG) and very low-density lipoprotein (VLDL). Atherogenic index of plasma (AIP) was calculated using a standard formula. Statistical Analysis Used: Independent sample t-tests were used to determine the statistical significance of mean values between the case and control groups. Pearson’s correlation test was used to correlate various components of the lipid profile and the atherogenic index with DAS28-ESR. Results: Significantly reduced levels of HDL (39.31 ± 6.52 mg/dl) were found in patients with RA as compared to the healthy controls. Serum TG was significantly higher in the cases (138.35 ± 39.23 mg/dl). TC level was significantly elevated in the cases. Mean atherogenic index in cases was significantly higher (0.17 + 0.14) in some cases. Only a weak correlation was found between lipid profile components and DAS28-ESR. Conclusions: Serum HDL level was significantly lower, and TC, TG levels and AIP were significantly higher in younger patients of early DMARD naïve RA pointing to a higher CV risk.